The homogenization of China's city flowers and city trees - Zhuo Cheng; Ziyi Wu; Weizhe Chen; Wenxuan Li; Chen Lin; Qing Zhang; Chunlin Long (People and Nature)
Abstract Cultural homogeneity, similar to the loss biodiversity, is a significant global issue that is increasingly gaining attention. City flowers and city trees (CFTs) serve as emblematic cultural symbols of modern cities, often referred to as the ‘green business card’. While many cities have established CFTs in recent decades, there are instances of inconsistencies and irrationalities in the selection process. This study conducts a statistical analysis of CFTs in prefecture‐level cities in China, detailing their distribution, species diversity, historical evolution, establishment reason and applications. China has designated city flowers for 270 cities and city trees for 256 cities, employing over 75 kinds of city flowers and 94 species of city trees. The top 10 plants selected as city flowers represent 66.7% of all designated city flowers, while the top 10 plants chosen as city trees account for 60.5% of all designated city trees. The main reasons for the establishing CFTs are culture and landscape. It is noteworthy that in cities where CFTs are implemented for reasons that remain unclear, they constitute 20.4% and 26.6%, respectively. It has been determined that most of the CFTs are used for urban greening, with 80% of the city's flowers, and 84% of the city's trees being used. Our study highlights the high level of species homogeneity among CFTs in China and identifies the lack of clarity in the rationale behind their selection in many cities. The study provides recommendations to address these issues and offers insights for cities that have yet to determine their CFTs. Read the free Plain Language Summary for this article on the Journal blog.